2013
DOI: 10.1371/journal.pone.0057425
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Premotor Cortical Excitability after Cathodal Inhibition of the Primary Motor Cortex: A Sham-Controlled Serial Navigated TMS Study

Abstract: BackgroundPremotor cortical regions (PMC) play an important role in the orchestration of motor function, yet their role in compensatory mechanisms in a disturbed motor system is largely unclear. Previous studies are consistent in describing pronounced anatomical and functional connectivity between the PMC and the primary motor cortex (M1). Lesion studies consistently show compensatory adaptive changes in PMC neural activity following an M1 lesion. Non-invasive brain modification of PMC neural activity has show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
3
18
0
Order By: Relevance
“…Although 80% of RMT was reported as the optimal conditioning intensity for SICI and ICF , this optimal value may be differentially modulated based upon in the specific rTMS parameters. As demonstrated by previous studies, both ISI and conditioning intensity significantly affect the responses of SICI and ICF . Following low‐frequency rTMS, some subjects may respond with inhibited responses while others are facilitated to the same test .…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Although 80% of RMT was reported as the optimal conditioning intensity for SICI and ICF , this optimal value may be differentially modulated based upon in the specific rTMS parameters. As demonstrated by previous studies, both ISI and conditioning intensity significantly affect the responses of SICI and ICF . Following low‐frequency rTMS, some subjects may respond with inhibited responses while others are facilitated to the same test .…”
Section: Discussionmentioning
confidence: 56%
“…The differences between outcome excitability assessment measures (SICI, ICF, and CSP) in response to low‐frequency rTMS may be due to the different cortical inhibitory mechanisms measured and the sensitivity of each outcome, which has been reported to be interrelated . The LTD‐like effect induced by low‐frequency rTMS with the present parameters might affect these three mechanisms differentially , suggesting that CSP is the most sensitive to the modulations performed, but other modulations may affect other measures differently. One consideration regarding the paired‐pulse assessments is that the ISIs and conditioning pulse intensity of SICI and ICF were not optimized for individual participants.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Baudewig et al, 2001;Kim et al, 2012;Lang et al, 2005;Polania et al, 2011)). On this line, it was recently observed that the downregulation of cortical excitability in the hand M1 increased the excitability in the ipsilateral premotor cortex (Schmidt et al, 2013). Therefore, we cannot exclude the possibility that by applying the stimulation over the leg M1 the supplementary and premotor areas were also indirectly stimulated.…”
Section: Discussionmentioning
confidence: 83%
“…The PMC has been previously highlighted as a key region for adaptive processes in the motor system, particularly in the case of reduced M1 function. Behaviorally meaningful adaptations have been demonstrated in PMC after M1 lesions in animals and humans (62) and non-invasive brain stimulation suppressing M1 excitability (63), indicating that functional compensation may depend on PMC activity. Further, other studies have demonstrated age-related increases in PMC activation during motor tasks (5,9,64), and some of this work has additionally suggested that this activation may become increasingly useful with aging (64).…”
Section: The Pmc and Pfc As Compensatory Resourcesmentioning
confidence: 99%